2015
DOI: 10.5897/ajb2014.14132
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and biofungicidal properties of maize rhizobacteria for growth promotion and plant disease resistance

Abstract: Plant growth promoting rhizobacteria (PGPR) are known to influence plant growing both by direct and/or indirect mechanisms. This study aimed to establish PGPR profile of 15 bacteria isolated from maize (Zea mays L.) rhizosphere in Benin. These rhizobacteria were screened in vitro for the plant growth promoting traits like production of indole acetic acid (IAA), ammonia (NH 3), hydrogen cyanide (HCN), catalase, exopolysaccharides and antifungal activity against phytopathogenic fungi for example Fusarium vertici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 19 publications
(18 reference statements)
1
6
0
Order By: Relevance
“…In the North, the yield (48.34%) of plants treated with P. putida + ½ dose of NPK and Urea was lower compared to that obtained in the Center. The work carried out by these authors, [48,39], reported that the PGPR rhizobacteria including P. putida used in this study strongly produce indole acetic acid (AIA), ammonia (NH3), hydrocyanic acid (HCN) and exopolysaccharides. The significant improvement in grain yield obtained would be related to the multifunctional properties of P. putida.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In the North, the yield (48.34%) of plants treated with P. putida + ½ dose of NPK and Urea was lower compared to that obtained in the Center. The work carried out by these authors, [48,39], reported that the PGPR rhizobacteria including P. putida used in this study strongly produce indole acetic acid (AIA), ammonia (NH3), hydrocyanic acid (HCN) and exopolysaccharides. The significant improvement in grain yield obtained would be related to the multifunctional properties of P. putida.…”
Section: Discussionmentioning
confidence: 90%
“…These results are in line with those of [20] who obtained a 27.29% increase with P. putida + chitosan + ½ dose of NPK and Urea compared to the control. The rhizobacteria P. putida under study is capable of solubilizing phosphate [39] and promoting a better absorption of nutrients by plants from the soil [18]; which would justify the results obtained with inoculated plants. Moreover, it has been reported that the larger the leaf area, the more plants achieve good photosynthesis, which is favourable to better productivity [40].…”
Section: Discussionmentioning
confidence: 93%
“…Several authors argue that PGPR can promote the plant growth through various mechanisms such as the nitrogen fixation (N2) and trace elements solubilization such as phosphate (P), inhibition of ethylene synthesis by the plant, the synthesis of plant hormones or vitamins and by decreasing the toxicity of heavy metals (Whipps, 2001;Dobbelaere et al, 2003;Cakmakci et al, 2006;Orhan et al, 2006). Noumavo et al (2015) reported that the rhizobacteria strongly produced Indole Acetic Acid (IAA), ammonia (NH3), hydrogen cyanide (HCN), exopolysaccharides and exhibit strong antifungal activity against Fusarium verticillioides, real pathogen of maize.…”
Section: Discussionmentioning
confidence: 99%
“…Noumavo et al [8] observed a clear improvement of in vitro maize seeds germination and greenhouse growth after seeds inoculation by PGPR and their various combinations. These rhizobacteria have strongly produced Indole Acetic Acid (IAA), ammonia (NH 3 ), hydrogen cyanide (HCN), and exopolysaccharides and exhibit strong antifungal activity against Fusarium verticillioides , real pathogen of maize [9]. …”
Section: Introductionmentioning
confidence: 99%
“…Indeed, chitosan is a natural polymer derived from chitin, commonly founded in the carapace of crustaceans, insect cuticle, and fungi walls [11]. This biopesticide is also a stimulator of flowering and fruition [12] and also used as a plant growth regulator [9]. …”
Section: Introductionmentioning
confidence: 99%